2017
DOI: 10.1002/2017gl072879
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical systems approach to studying midlatitude weather extremes

Abstract: Extreme weather occurrences carry enormous social and economic costs and routinely garner widespread scientific and media coverage. The ability to predict these events is therefore a topic of crucial importance. Here we propose a novel predictability pathway for extreme events, by building upon recent advances in dynamical systems theory. We show that simple dynamical systems metrics can be used to identify sets of large‐scale atmospheric flow patterns with similar spatial structure and temporal evolution on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 34 publications
3
89
0
Order By: Relevance
“…The intensified zonal flow seen in the DWB+ period and the associated westerly advection penetrates into the continent resulting in heightened rates of warm extremes over Eastern Europe. Wintertime warm extremes can have significant impact on local economies by modulating snow and water availability and crop yields (e.g., Gooding et al 2003;Beniston 2005), and have previously been linked to similar large-scale circulation anomalies over the North Atlantic (Messori et al 2017). A similarly large change is seen in the occurrence of extreme 10-m wind episodes and in wind destructiveness.…”
Section: Discussionmentioning
confidence: 94%
“…The intensified zonal flow seen in the DWB+ period and the associated westerly advection penetrates into the continent resulting in heightened rates of warm extremes over Eastern Europe. Wintertime warm extremes can have significant impact on local economies by modulating snow and water availability and crop yields (e.g., Gooding et al 2003;Beniston 2005), and have previously been linked to similar large-scale circulation anomalies over the North Atlantic (Messori et al 2017). A similarly large change is seen in the occurrence of extreme 10-m wind episodes and in wind destructiveness.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the critical transition to a turbulent state has exponents comparable to those of directed percolation, concerning, for example, the scaling of the number of active sites in terms of distance to the critical governing parameter of the transition. Such an analysis also shows the importance of large-scale zonal flows (Shih et al, 2016) of critical layers (Park et al, 2018), as well as that of regeneration self-sustaining cycles in such flows (Kawahara & Kida, 2001;Waleffe, 1997) with, citing Mckeon (2017), "the importance of scale interactions in sustaining wall turbulence through the nonlinear term. "…”
Section: 1029/2018ea000432mentioning
confidence: 98%
“…In dynamical systems terms, these fields represent projections of the full phase-space dynamics onto specific subspaces, called Poincaré sections. In Faranda et al (2016) and Messori et al (2017) we have shown that d and θ can be used to characterize regional-scale atmospheric fields and further provide information on the predictability linked to a given atmospheric state. It is therefore important to investigate these indicators at different spatial scales to fully understand the insights they can provide.…”
Section: Introductionmentioning
confidence: 99%